Implementation of Service Quality, Infrastructure, and Accessibility for Light Rail Transit (LRT) Transportation: Study Literature Review - Muhammad Tohir; Andri Primadi; Cecep Budiman; Lira Agusinta; Mulyadi Mulyadi (Dinasti International Journal of Education Management And Social Science, 2025)
The article on the implementation of service quality, infrastructure and accessibility to light rail transit (LRT) transportation is an article within the scope of marketing management science. The purpose of this study is to build a hypothesis regarding the influence between variables that can later be used for further research within the scope of marketing management. The research method used is descriptive qualitative. The data collection technique uses literature studies/literature reviews. Data were obtained from previous studies that are relevant to this study and sourced from academic online media such as Publish or Perish, Google Scholar, Jurnal Sinta, DOAJ and Garuda. The results of this study are as follows: 1) Service quality plays a role in light rail transit (LRT) transportation; 2) Infrastructure plays a role in light rail transit (LRT) transportation; and 3) Accessibility plays a role in light rail transit (LRT) transportation.